Henry James’s Permanent Adolescence - Bradley, J. author. aut Link
XI, 162 p. 1 illus.
Keywords: Henry James remained throughout his life focused on his boyhood and early manhood, and correspondingly on younger boys and men, and John R. Bradley illustrates how it is in the context of such narcissism that James consistently dealt with male desire in his fiction. He also traces a more subtle but related trajectory in James's writing from a Classical to a Modernist gay discourse, which in turn is shown to have been paralleled by a shift in James's fiction from naturalistic beginnings to later stylistic evasion and obscurity. This radical book, which covers the whole of James's career, will quickly be recognized as a defining text in this emerging field of James studies.